2010
DOI: 10.2139/ssrn.1569580
|View full text |Cite
|
Sign up to set email alerts
|

The Electricity Consumption and Economic Growth Nexus in Pakistan: A New Evidence

Abstract: This study examines the Granger causality between electricity consumption and Gross Domestic Product WALD test (T-Y test) affirm the existence of unidirectional Granger causality from electricity consumptionto economic growth without any feedback effect. Therefore, an immediate effort to increase electricity availability is required and energy conservation policies are supposed to halt the economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
6
11
0
Order By: Relevance
“…We find that 0.291% energy consumption is increased due to 1% increase in economic growth. Our results are in line with the findings of Qazi and Riaz (2008), Atif and Siddiqi (2010). Therefore, the coefficient of CO 2 emissions is 0.450 and highly significant at the 1% level.…”
Section: Main Results and Discussionsupporting
confidence: 92%
“…We find that 0.291% energy consumption is increased due to 1% increase in economic growth. Our results are in line with the findings of Qazi and Riaz (2008), Atif and Siddiqi (2010). Therefore, the coefficient of CO 2 emissions is 0.450 and highly significant at the 1% level.…”
Section: Main Results and Discussionsupporting
confidence: 92%
“…In the study of Masuduzzaman (2012), three variables (electricity consumption, GDP and investment) were modeled for Bangladesh and the results confirmed the existence of a unidirectional causality running from electricity consumption to economic growth. Similarly, Atif and Siddiqi (2010) provided new evidence on the relationship between electricity consumption and economic growth for Pakistan. They found the existence of a unidirectional granger causality from electricity consumption to economic growth using the standard granger causality test and the modified WALD test.…”
Section: Brief Review Of Literaturementioning
confidence: 99%
“…Siddiqui (2004) concluded that higher economic growth is caused by energy expansion and vice versa in Pakistan. Atif and Siddiqi (2010) analyzed the association between energy consumption and GDP in Pakistan from 1971 to 2007. The findings suggested the long-run relationship and the unidirectional causality running from energy consumption to GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An uninterrupted energy supply is extremely crucial for sustainable economic development (Atif and Siddiqi 2010). It is believed that energy is the lifeblood of the economy, which is subject to policies and market forces of demand-supply.…”
Section: Introductionmentioning
confidence: 99%